Analysis Of Financial Management In An Effort To Increase Revenue At Mini Waterpark - Sarunsang, Rayessa; Tarigan , Heskyel Pranata (Journal of Applied Financial Management, 2025)
This study aims to determine the application of financial management carried out by Mini Waterpark in an effort to increase revenue. This research is a type of field research with a descriptive qualitative approach. The type of data used in this study is primary data obtained through direct interviews between researchers and Mini Waterpark as an informant, and secondary data used is data obtained through data that has been researched and collected by other parties related to research problems. as well as in the form of literature books and research journals regarding theories that are considered relevant to the research theme that are used as reference materials in research, especially human resource management literature on motivation and work spirit. Data collection methods are literature, observation, interviews and documentation. And the data obtained will be analyzed using a theoretical basis, data reduction data presentation for problem solving so as to get conclusions and suggestions. The results of this study are that Mini Waterpark has been able to manage its finances quite well although it still has some obstacles in running it, this can be seen through the increase in revenue of Mini Waterpark from January to 2 June 2024 and the way Mini Waterpark in financial management, namely pass the financial planning stage, create an organizational structure and segregation of functions, regulate financial circulation, make financial reports and the last one always evaluates financial management.